Acute normovolemic hemodilutlon: advantages and limitations - Ellenberger, Christoph; Licker, Marc (Revue médicale suisse, 2006)
Although arterial oxygen content is decreased after acute normovolemic hemodilution (ANH), blood rheology is improved and cardiac output is increased through increased venous return. To meet metabolic demand, tissue oxygen extraction is increased and the sympathetic nervous system is activated only in awake subjects. In man, hemoglobin levels of < 40-50 g/L may induce anaerobic cell metabolism. The transfusion threshold should take into account the individual patient metabolic needs and the associated cardio-pulmonary diseases. Better tissue blood flow distribution and erythropoietin liberation resulting from ANH may potentially attenuate myocardial ischemic injuries. ANH is poorly effective in reducing the necessity of allogenic blood transfusion, especially in centres where a restrictive transfusion policy is already implemented.